Genetic divergence in novel determinate variants of resynthesized Indian mustard (Brassica juncea (L.) Czern & Coss) - Kaur, Harjeevan; Banga, S.S. (The Indian Journal of Genetics and Plant Breeding, 2016)
A field experiment was conducted to study the genetic diversity in 125 genotypes with determinate plant growth habit in Brassica juncea along with 3 indeterminate check varieties PBR 357, Coral 432 and DMH 1 as per alpha lattice design with two replications at PAU,Ludhiana.Mahalanobis’ D2 analysis grouped genotypes into 12 clusters. Clusters 1, 2 and 6 were considered ideal for future breeding efforts based on inter genotypic distance and other agronomic performance. Out of the fifteen traits evaluated, yield (kg/ha) and pods/plant contributed the most towards the divergence (81.06% and 18.58%, respectively).